Recent Progress of Quantum Dot Lasers Monolithically Integrated on Si Platform - Cao, Victoria; Park, Jae-Seong; Tang, Mingchu; Zhou, Taojie; Seeds, Alwyn; Chen, Siming; Liu, Huiyun (Frontiers in Physics, 2022)
With continuously growing global data traffic, silicon (Si)-based photonic integrated circuits have emerged as a promising solution for high-performance Intra-/Inter-chip optical communication. However, a lack of a Si-based light source remains to be solved due to the inefficient light-emitting property of Si. To tackle the absence of a native light source, integrating III-V lasers, which provide superior optical and electrical properties, has been extensively investigated. Remarkably, the use of quantum dots as an active medium in III-V lasers has attracted considerable interest because of various advantages, such as tolerance to crystalline defects, temperature insensitivity, low threshold current density and reduced reflection sensitivity. This paper reviews the recent progress of III-V quantum dot lasers monolithically integrated on the Si platform in terms of the different cavity types and sizes and discusses the future scope and application.